Tinjauan Pengaturan Hukum Konservasi Sumber Daya Alam Hayati dalam Berbagai Putusan Mahkamah Konstitusi - Luthfi Widagdo Eddyono (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Law No. 5 Year 1990 on Conservation of Biological Resources and Ecosystem must be relevant and in harmony with regulation and Constitutional Court decisions. The issues of this article are : (1) How is the harmony between Law No. 5 Year 1990 on Conservation of Biological Resources and Ecosystem with other regulations ?; 2) how is the accordance between Law No. 5 Year 1990 on Conservation of Biological Resources and Ecosystem with Constitutional Court decisions? This is a normative research with conceptual and regulations approach. This article use secondary data with interactive model analysis. This research shows that : (1) Law No. 5 Year 1990 on Conservation of Biological Resources and Ecosystem has not considered Basic Agrarian Law and People’s Consultative Assembly No. IX/MPR/2001 as base of natural resources regulation. This regulation is neither according to other regulations nor responsive because this has not regulated modern biotechnology and genetic resources. (2) Law No. 5 Year 1990 on Conservation of Biological Resources and Ecosystem is not according to Constitutional Court Decision that emphasize on preventive aspect of natural resources management, protection and respect of indigenous people and substantive public participation. In another side, this regulation emphasize on curative aspect, irrespect and not protect indigenous people. This article recommends revision of this regulation and accord it with Constitutional Court Decision.